THE THEORETICAL FOUNDATIONS OF INSTITUTIONALISM AT THE STAGE OF ACCELERATING GLOBALIZATION OF INTERNATIONAL ECONOMIC RELATIONS - Salamova,; Turovsky, Alexander (Revista Inclusiones, 2020)
The globalization of the world economy in modern conditions is a priority trend that determines the world socio-economic development of countries. Analysis of the patterns of globalization is an important research task. One of the most important features of globalization of the world economy is its systemic character. The change in the structure of the world economy is associated with the emergence of regional economic associations. Under the influence of globalization processes, the content of already functioning institutions of the world economy is changing and new institutional structures are being formed. One of the most promising theoretical and methodological approaches is the institutional approach to the analysis of patterns of globalization of the world economic, which allows analyzing the formation and development of institutions in the economic space of new megaregions - regional economic associations. The article describes the current approaches to the study of the institutionalization of international economic relations and the emergence of a new system of supranational institutions acting regulators of global economic development.